Tectonic evolution and its control on oil–gas accumulation in southern East China Sea since the Jurassic - Wang, Mingjian; Jiang, Xingchao; Lei, Baohua; Huang, Long; Pan, Jun (Frontiers in Earth Science, 2023)
Based on previous research results on Mesozoic magmatic rocks and volcanic age as well as tectonic environments in northern South China Sea and southern East China Sea (NSCS-SECS) , geophysical field characteristics, strata development and seismic facies characteristics in NSCS-SECS which were viewed as an entirety were investigated. These research results were combined with analysis results of balanced profile evolution to reproduce the tectonic evolution of SECS since Jurassic. On this basis, burial history of wells and simulation wells in SECS were analyzed using data of well drilling, seismic and source rocks. Moreover, favorable oil-gas accumulation modes in Lower-Middle Jurassic were proposed by combining with studies on oil-gas accumulation elements and conditions. Results demonstrated that NSCS-SECS had consistent tectonic setting and comparable strata from Jurassic to Cretaceous. They were a unified large basin in this period. The basin has experienced two evolutionary stages, respectively, fore-arc depression basin in Early-Middle Jurassic (J1-2) and back-arc faulted basin in Late Jurassic-Cretaceous (J3-K). There was extensive development of dark mudstones in SECS during Lower-Middle Jurassic. In particular, Keelung Sag was the depositional center with large thickness of Lower-Middle Jurassic source rocks and it had entered into high-maturity stage. And Keelung Sag was the hydrocarbon generation center in the study area. From northwest to southeast, hydrocarbon generation process of Lower-Middle Jurassic source rocks became increasingly complicated. Lower-Middle Jurassic source rock in northwest edges of the basin experienced twice hydrocarbon generation processes, while Keelung Sag toward the southeast experienced three hydrocarbon generation processes. Oil-gas accumulation modes and types in different evolutionary stages were different due to control by tectonic evolution. Oil and gas which was produced by Lower-Middle Jurassic source rocks in the Keelung Sag migrated to the west high tectonic units and accumulated here. Research conclusions provided references to Mesozoic oil-gas exploration in NSCS-SECS.